1997
DOI: 10.1359/jbmr.1997.12.12.2082
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps and Grip Strength Are Related to Vitamin D Receptor Genotype in Elderly Nonobese Women

Abstract: ), the BMD in the FN was 5% higher in women with the bb BsmI genotype than in women with the BB genotype ( p < 0.05). After correction for muscle strength, no association was found. A significant association between the VDR genotypes and quadriceps and grip strength was observed. In nonobese women, a 23% difference in quadriceps strength ( p < 0.01) and 7% in grip strength (NS) was observed between the bb and BB genotype of the VDR. After correction for confounding factors and BMD, this association was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 37 publications
2
118
1
2
Order By: Relevance
“…This has been confirmed as a histological atrophy of muscle, predominantly type II fibres and is exacerbated by ageing (Janssen et al 2002) (Roth et al 2004), with a different polymorphism linked with muscle strength in a further study of older women (Geusens et al 1997). In a longitudinal study looking at sarcopenia in older men and women, low vitamin D was linked with increased risk (by approximately !2) of reduced muscle mass and strength.…”
Section: Specific Endocrine Systemsmentioning
confidence: 74%
“…This has been confirmed as a histological atrophy of muscle, predominantly type II fibres and is exacerbated by ageing (Janssen et al 2002) (Roth et al 2004), with a different polymorphism linked with muscle strength in a further study of older women (Geusens et al 1997). In a longitudinal study looking at sarcopenia in older men and women, low vitamin D was linked with increased risk (by approximately !2) of reduced muscle mass and strength.…”
Section: Specific Endocrine Systemsmentioning
confidence: 74%
“…However, only a few specific genetic variants have been suggested to affect some of the phenotypes reflecting physical functioning. The findings from these and other studies have mostly been based on selected populations [i.e., young healthy males and elite athletes; Montgomery et al, 1998;Williams et al, 2000;Gayagay et al, 1998;Myerson et al, 1999] and have not been consistent [Taylor et al, 1999;Rankinen et al, 2000a,b;Frederiksen et al, 2002], or the association was confined to subgroups within the study sample [Geusens et al, 1997]. With respect to physical functioning, various different phenotypes [e.g., self-report; Christensen et al, 2000], a proportion of fast-twitch and slow-twitch fibers in skeletal muscle biopsies [Simoneau and Bouchard, 1995], magnetic resonance imaging of muscle mass [Gibbons et al, 1998], and measurement of maximal aerobic power (VO 2-max ) [Sundet et al, 1994] have been used in different studies, all of which suggested a genetic component to physical functioning.…”
Section: Introductionmentioning
confidence: 82%
“…One suggestion has been a polymorphism in the gene encoding the Angiotensin Converting Enzyme, but the association was found only in small samples of young healthy males and elite athletes [Montgomery et al, 1998;Williams et al, 2000;Gayagay et al, 1998;Myerson et al, 1999], and not in all studies [Taylor et al, 1999;Rankinen et al, 2000a,b] and not among the elderly [Frederiksen et al, 2002]. A polymorphism in the gene encoding a receptor for vitamin D has been associated with grip strength in postmenopausal women, but only in a nonobese subgroup [Geusens et al, 1997]. No association between a polymorphism in the estrogen receptor gene and strength was found in another study of postmenopausal women [Vandevyver et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found an association between VDR BsmI genotypes and muscle strength in postmenopausal women (Vandevyver et al 1999) and in healthy (non-obese) old women (Geusens et al 1997), with bb individuals exhibiting significantly higher quadriceps strength than those with the BB genotype, yet this association was not corroborated in obese old women (Geusens et al 1997). Hopkinson et al (2008) reported that the b allele of the BsmI polymorphism was associated with greater quadriceps strength in patients with chronic obstructive disease, but had no effect in healthy controls.…”
Section: Cross-sectional Genetic Association Studiesmentioning
confidence: 99%